Identification of the drug-use behaviors of the elderly living in nursing homes - Oguzoncul, Ayse Ferdane; Ercan, Emel; Celebi, Evrim (Dove Medical Press Ltd, 2018)
Objective: As our society ages, the incidence of acute and chronic diseases increases, and so does chronic drug use and polypharmacy. This study was intended to examine the medication behaviors of the elderly who lived in the nursing homes in the Elazig and Malatya provinces, located in eastern Turkey, and in the Kayseri province located in Central Anatolia. Materials and methods: The population of this cross-sectional study included people over the age of 60 years (n=310) who lived in the nursing homes in the Elazig, Malatya, and Kayseri provinces. The entire population was included in the research without sampling, of which 255 (82.2%) people participated. Data were collected using a survey form, and the survey was conducted through face-to-face interviews. The data were reported in numbers, percentages, and averages. Results: Of the studied population, 87.8% were treated through polypharmacy, using various drugs. The most commonly used drugs were antihypertensives (52.2%). Females over 60 years used more polypharmacy than men (p<0.05). Of the elderly studied, 97.3% used drugs as recommended, 95.3% did not know about the side effects of the drugs they used, and 93.7% did not read the prospectuses of the drugs. Also, 82.7% stated that their drugs did not have any side effects and 70.2% said that the health care personnel did not educate them about their drugs. Of the elderly who were informed about their drugs, 55.3% obtained the information from the nurse and 44.7% from the physician. Of the elderly, 51.3% received education on the duration they would need to take the drug, 30.3% were educated on the intended use of the drugs, 7.9% received education on their drug dose, and 6.6% were educated on the side effects of the drugs. Conclusion: The results of this study showed that the majority of the elderly studied used more than one drug (polypharmacy) and the most used drug group was antihypertensives.
Keywords: elderly; nursing home; drug-use